Excimer based fluorescent pyrene–ferritin conjugate for protein oligomerization studies and imaging in living cells. Issue 23 (3rd April 2018) - Benni, Irene; Trabuco, Matilde Cardoso; Di Stasio, Enrico; Arcovito, Alessandro; Boffi, Alberto; Malatesta, Francesco; Bonamore, Alessandra; De Panfilis, Simone; de Turris, Valeria; Baiocco, Paola
Abstract : Pyrene fluorescence changes upon ferritin self-assembly allowed to establish the kinetic and thermodynamic details of the archaeal ferritins oligomerization mechanism and was successfully visualized in vitro by two photon fluorescence microscopy. Abstract : Ferritin self-assembly has been widely exploited for the synthesis of a variety of nanoparticles for drug-delivery and diagnostic applications. However, despite the crucial role of ferritin self-assembly mechanism for probes encapsulation, little is known about the principles behind the oligomerization mechanism. In the present work, the novel "humanized" chimeric Archaeal ferritin HumAfFt, displaying the transferrin receptor-1 (TfR1) recognition motif typical of human H homopolymer and the unique salt-triggered oligomerization properties of Archaeoglobus fulgidus ferritin (AfFt), was site-selectively labeled with N -(1-pyrenyl)maleimide on a topologically selected cysteine residue inside the protein cavity, next to the dimer interface. Pyrene characteristic fluorescence features were exploited to investigate the transition from a dimeric to a cage-like 24-meric state and to visualize the protein in vitro by two photon fluorescence microscopy. Indeed, pyrene fluorescence changes upon ferritin self-assembly allowed to establish, for the first time, the kinetic and thermodynamic details of the archaeal ferritins oligomerization mechanism. In particular, the magnesium induced oligomerization proved to be faster than the monovalent cation-triggered process, highly cooperative, complete at low MgCl2 concentrations, and reversed by treatment with EDTA. Moreover, pyrene intense excimer fluorescence was successfully visualized in vitro by two photon fluorescence microscopy as pyrene-labeled HumAfFt was actively uptaken into HeLa cells by human transferrin receptor TfR1 recognition, thus representing a unique nano-device building block for two photon fluorescence cell imaging.